Effect of potassium humate spray on some biochemical characteristics in potato leaves Solanum tuberosum under water stress conditions - Hadia Hassan; Sawsan Suleiman; Maher Dais (مجلة بغداد للعلوم)
The research was carried out at Al-Hanadi Research Station - Lattakia Agricultural Scientific Research Center, during spring season 2020 .To experience the effect of different potassium humate levels 500,1000,1500 ppm  as a foliar spray on potato leaves variety Spunta , at 40 and 80% of field capacity humidity . The research involved four treatments with 3 replicates   at each irrigation level. A Completely Randomized design was used. Plants were sprayed with potassium humate HA three times, with an interval of ten days after 35 days of planting.